ON THE IMPACT OF FLIGHT SAFETY CERTIFICATION REQUIREMENTS ON THE AERODYNAMIC EFFICIENCY OF COMMERCIAL AIRPLANES - V. I. Shevyakov (Научный вестник МГТУ ГА, 2018)
The article considers the issue of aerodynamics efficiency implementation taking into account certification requirements for flight safety. Aerodynamics efficiency means high aerodynamic performance (depending on the airplane size), aerodynamic performance in cruise flight, high aerodynamic performance at takeoff, as well as lift performance at landing.The author estimated the impact on aerodynamics efficiency of both the requirements for aerodynamics performance and requirements for aircraft systems, noncompliance with which may result in significant change of expected operating conditions. It was shown that the use of supercritical wing profiles may result in flight mode limitations due to failure of the required buffeting capacities. It does not allow engaging all the advantages of aerodynamics layout and requires special design solutions to prevent such cases.There were reviewed certification requirements for flight level pressure altitude accuracy and icing conditions warning sysytem. The research presented the methods of aerodynamic efficiency increase by meeting the requirements for reduced vertical separation minima flights and in icing conditions, including requirements for air data probes. Reduced vertical separation minima flight requirements are met by means of efficient air data probes location. Theoretical methods of flow calculation determine areas on the airplane skin surface where static probes minimize errors depending on angle-of-attack and sideslip. It was shown that if certification requirements are not met and in case of flight out of reduced vertical separation minima area, aerodynamics efficiency is significantly reduced and fuel consumption can be increased by 10% and higher. Suggested approaches implementation allows increasing commercial airplanes competitiveness.